2017
DOI: 10.1371/journal.pone.0186856
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rhythm control strategies versus rate control strategies for atrial fibrillation and atrial flutter: A systematic review with meta-analysis and Trial Sequential Analysis

Abstract: BackgroundAtrial fibrillation and atrial flutter may be managed by either a rhythm control strategy or a rate control strategy but the evidence on the clinical effects of these two intervention strategies is unclear. Our objective was to assess the beneficial and harmful effects of rhythm control strategies versus rate control strategies for atrial fibrillation and atrial flutter.MethodsWe searched CENTRAL, MEDLINE, Embase, LILACS, Web of Science, BIOSIS, Google Scholar, clinicaltrials.gov, TRIP, EU-CTR, Chi-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 118 publications
0
36
1
1
Order By: Relevance
“…After the propensity score matched analysis for comparison between these treatment strategies, the incidence rate of ischemic stroke (0.1% vs. 1.0%) in [26,27]. Classic trials comparing the rate versus rhythm control strategy with only antiarrhythmic drugs such as the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, RAte Control versus Electrical cardioversion (RACE), and The Atrial Fibrillation and Congestive Heart Failure (AF-CHF) trial showed a non-statistically significant higher incidence of ischemic stroke in the rate control strategy, and recent comparisons of the differences between the rhythm and rate control strategy also showed that the occurrence of stroke seems to be similar with an overall odds ratio of 0.99 (95% confidence interval [CI], 0.75 to 1.30) and a risk ratio (RR) of 0.96 (95% CI, 0.68 to 1.34) [9,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…After the propensity score matched analysis for comparison between these treatment strategies, the incidence rate of ischemic stroke (0.1% vs. 1.0%) in [26,27]. Classic trials comparing the rate versus rhythm control strategy with only antiarrhythmic drugs such as the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, RAte Control versus Electrical cardioversion (RACE), and The Atrial Fibrillation and Congestive Heart Failure (AF-CHF) trial showed a non-statistically significant higher incidence of ischemic stroke in the rate control strategy, and recent comparisons of the differences between the rhythm and rate control strategy also showed that the occurrence of stroke seems to be similar with an overall odds ratio of 0.99 (95% confidence interval [CI], 0.75 to 1.30) and a risk ratio (RR) of 0.96 (95% CI, 0.68 to 1.34) [9,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not found superiority of rhythm control over rate control in broad patient populations with sustained types of AF 40‐42 . Moreover, some interventions could also worsen the outcome due serious adverse effects, 17,18 but the impact on patient‐important outcomes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation was diagnosed by cardiologists depending on clinical findings or irregular pulse and a pulse deficit of >15, the diagnosis was confirmed by electrocardiogram according to the American College of Cardiology Guidelines (10). The data were collected by the first and second authors.…”
Section: Data Collectionmentioning
confidence: 99%